Recent and Frequent Vertigo Attacks Produce Negative Findings on Furosemide-Loading Vestibular Evoked Myogenic Potential Testing in Meniere's Disease - Seo, Toru; Shiraishi, Ko; Kobayashi, Takaaki; Fujita, Takeshi; Saito, Kazuya; Doi, Katsumi (Frontiers in Neurology, 2018)
Objective: The peak-to-peak amplitude of the p13-n23 wave in cervical vestibular evoked myogenic potential can increase after furosemide administration in patients with Meniere’s disease (furosemide-loading VEMP [FVEMP] testing). The examination is used to test for the presence of endolymphatic hydrops; we investigated factors that may influence the results. Methods: Forty-two subjects (23 males and 19 females, aged 24 to 70 years) with unilateral definite Meniere’s disease who underwent FVEMP testing were retrospectively studied. Possible factors associated with the results of FVEMP testing were studied using logistic regression analysis. Results: Ages, sex, affected side, stage, disease duration, and mean hearing level of pure tone audiometry did not influence the results of FVEMP testing in the univariate analysis (p > 0.05). Number of days since the last vertigo attack (odds ratio [OR]: 1.07, p = 0.031) and frequency of vertigo attacks per month (OR: 0.42, p = 0.003) were significantly associated with the results of testing. Multivariate analysis showed that both days since the last vertigo attack < 7 (OR: 0.13, p = 0.04) and frequency of vertigo attacks per month ≥ 2 (OR: 0.06, p = 0.004) were risk factors for negative results on FVEMP testing. Conclusion: This study found that recent and frequent vertigo attacks produced negative findings on FVEMP testing in Meniere’s disease. This apparently irrational finding can be explained by the consequences of membranous labyrinth rupture during vertigo attacks; the altered saccular resonance due to discontinuity of the membranous labyrinth cannot be remedied by furosemide administration. FVEMP testing results may provide us with pathophysiological information regarding the membranous labyrinth.